Pelatihan Pengolahan Data yang Efektif Menggunakan Microsoft Excel Sekolah Madrasah Aliyah Swasta (MAS) Annida Al Islamy - Jatnika, Hendra; Marsela Tri Anggrainie; Muhammad Zaid Al Khair; Muh.Narya Nash; Tyara Anastasya; Joey Andrew Fransisco Sihombing; Azizah Arip Rambe; Grace Augustin Sinaga; Arfani Lovina Br Stendel; Rizka Putri Aulia Rusdi; Adinda Musika Permata; Mohamad Tanwirul Akbar; David Gabriel Sembiring; Muhamad Nur Khanib; Fakhri Faros; Naila Husnaa; M. Rafif Soniansyah; Ocha Nia Martcya Situmorang (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
MAS Annida Al Islamy is a high school that integrates general education and Islamic religion to form students who are academically competent and have good character. The school strives to improve the quality of education, including technical skills training such as Microsoft Excel to improve students' digital literacy. This service aims to improve basic data processing skills using Excel among students. The main challenge faced is the students' low ability to operate Excel, which hinders them in managing data efficiently. The method used was hands-on training with a participatory approach, covering introductory material on the interface, data filling, basic formulas, and making simple graphs. The training was supplemented with practical exercises and interactive Q&A sessions. The results showed an increase in participants' understanding and skills in using Excel. As a result, students are more confident in processing data and are better prepared to face academic and professional challenges in the digital era.